Non-negative constraint research of Tikhonov regularization inversion for dynamic light scattering - Wang, Y J; Shen, J; Liu, W; Sun, X M; Dou, Z H (Laser physics, 2013)
In dynamic light scattering (DLS) technology, a non-negative constraint on the solution can improve the inversion accuracy of the particle size distribution (PSD). Different non-negative constraint methods have different effects on the inversion results. Combined with the Tikhonov regularization inversion method, the following non-negativity constraint methods: negative to zero (N-to-Z), multi-negative to zero (Multi-N-to-Z), Lin-projected gradient (LPG), oblique projected Landweber (OPL), projected sequential subspace optimization (PSESOP), interior point Newton (IPN), gradient projection conjugate gradient (GPCG) and trust-region method based on the interior reflective Newton (TR-IRN) method are studied in DLS inversion. In different inversion ranges and noise levels, autocorrelation functions of unimodal and bimodal particle distributions were inverted using different non-negativity constraint methods. From the inversion results, the characteristics of the various methods were obtained, which can be treated as a reference for the implementation of non-negative constraints in Tikhonov regularization inversion of DLS.